2019
DOI: 10.1111/ppa.13027
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pierce's disease susceptibility in Vitis vinifera cultivars with different pedigrees

Abstract: Pierce's disease (PD) of grapevine is caused by the bacterium Xylella fastidiosa. In this study, an integrated approach was applied to assess PD susceptibility among different Vitis vinifera cultivars that incorporated disease severity, bacterial pathogen abundance and loss of stem xylem hydraulic conductivity. It was hypothesized that levels of PD susceptibility in V. vinifera can be attributed in part to the host anatomical features that are shaped by its pedigree background. Two popular wine grape cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 37 publications
3
36
0
Order By: Relevance
“…Indeed, Xylella colonization is significantly more extensive in Kalamata than FS17, which confirms, together with the limitedness of symptoms, the traits of resistance identified in the latter cultivar. Altogether, these results suggest that other mechanisms, likely controlling Xylella population size and its pathogenic effects by genetic [ 13 ] or anatomic [ 7 ] traits, may be responsible for this phenotype.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Indeed, Xylella colonization is significantly more extensive in Kalamata than FS17, which confirms, together with the limitedness of symptoms, the traits of resistance identified in the latter cultivar. Altogether, these results suggest that other mechanisms, likely controlling Xylella population size and its pathogenic effects by genetic [ 13 ] or anatomic [ 7 ] traits, may be responsible for this phenotype.…”
Section: Discussionmentioning
confidence: 92%
“…The ability to infect up to 595 plant species [ 5 ], together with the insect transmission [ 6 ] and the lack of effective treatments to cure infected plants [ 2 ], make the control of Xylella infections very challenging, requiring a compendium of integrated strategies relying on reducing vector population, eliminating sources of infections, and search for resistance traits in the affected species. Proofs of genetic resistance have been found in grape [ 7 , 8 ] and citrus [ 9 , 10 , 11 , 12 ] and more recently in olive cultivars Leccino and FS17 [ 13 , 14 , 15 , 16 , 17 ]. Even so, mechanisms underlying differential host responses to Xylella infections are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the case regarding the susceptibility of different species or varieties to specific pathogens (Jacobi & MacDonald, 1980;Ouellette et al, 1999;Clerivet et al, 2000;Et-Touil et al, 2005;Venturas et al, 2014;Park & Juzwik 2014;Rioux et al, 2018), in particular to Phaeomoniella chlamydospora, one of the pathogen associated with esca (Pouzoulet et al, 2017;. (ii) In other studies, it has been shown that tyloses can exacerbate symptoms (Talboys, 1972): they cause a reduction in stem hydraulic conductivity, sometimes associated with a reduction in stomatal conductance in leaves and, in the most severe cases, wilting (Parke et al, 2007;Beier et al, 2017;Lachenbruch & Zhao, 2019, Mensah et al, 2020Sun et al, 2013;Deyett et al, 2019 during Pierce's disease). Our results suggest that during esca (i) the development of tyloses in stems cannot be interpreted as a systematic trait of pathogen resistance because visual symptoms were observed despite the presence of tyloses and they were produced at a distance from pathogens.…”
Section: Hydraulic Conductivity Tyloses and Vessel Anatomymentioning
confidence: 99%
“…As these pathogens colonize the vascular system, the xylem conductivity of the host progressively decreases due to the occlusion of vessels by tyloses and gels triggered by the host in order to compartmentalize the infection (Pearce, 1996;Yadeta & Thomma, 2013). This loss of hydraulic conductivity has negative effects on the plant and according to the extent of infection can ultimately lead to plant death (Deyett et al, 2019;Inch & Ploetz, 2012).…”
Section: Introductionmentioning
confidence: 99%